IDENTIFICATION OF LANDSLIDE DISASTER BASED ON GEOMORPHOLOGICAL OBSERVATIONS IN GIRIPURWO VILLAGE, GIRIMULYO DISTRICT, KULONPROGO REGENCY, DIY - Tara, Ludgardis; Adi Prabowo, (ReTII, 2021)
The research area is located in Giripurwo Village, Girimulyo District, Kulonprogo Regency, DIY. Landslide potential is taken from four parameters such as slope, lithology, land use, and river density from the research area. These four parameters are then associated with the geomorphology and the intensity of landslides that occur in the study area. Landslide potential maps were made using the AHP (Analytical Hierarchy Process) method and ArcMap 10.8 software. The landslide potential level is divided into three, namely low landslide potential, medium landslide potential, and high landslide potential. From the results of the four-parameter overlay, it is known that Giripurwo has moderate potential for landslides in areas with dense-slightly sparse contour patterns having a height of >125 meters, lithology in the form of andesite and andesite breccias, land use is dominated by gardens and fields, and low river density. -medium. Low landslide potential is generally located in the southeastern part of Giripurwo with a loose contour pattern, >125 meters altitude, lithology in the form of sandstone, land use is dominated by rice fields and rainfed rice fields, medium to high river density. Mitigation can be done by making terraces and landslide retaining walls.